THE IMPACT OF LEADERSHIP, TRAINING AND EMPLOYEES’ INVOLVEMENT ON EMPLOYEES’ PERFORMANCE: A CASE STUDY OF AYAM PAK USU RESTAURANT (Outlet Jln. Merdeka) PONTIANAK - B12111029, ANDY GUNAWAN (Jurnal Manajemen Update, 2015)
The purpose of this study is to examine the impact of leadership, training, and employees’ involvement on employees’ performance. Primary data was gathered using questionnaire base on 40employees of Ayam Pak Usu Restaurant at Pontianak, interview with supervisor, and observation. The results of the study revealed that leadership, training, and employees’ involvement have significant impact on employees’ performance simultaneously while in partially shows that only training has significant impact on employees’ performance while leadership and employees’ involvement shows a positive impact but not significant on employees’ performance.     Keywords:   total   quality   management,   leadership,   training,   employees’ involvement, employees’ performance